Pathologic complete response of advanced hepatoid adenocarcinoma of the stomach following immuno-chemotherapy and conversion surgery: a rare case report and review of the literature - Li, Yaoqi; Wang, You; Yu, Tao; Wang, Dong; Ma, Hong; Ma, Jichun; Da, Mingxu (Frontiers in Oncology, 2025)
BackgroundHepatoid adenocarcinoma of the stomach (HAS) is a rare subtype of gastric cancer (GC) characterized by alpha-fetoprotein (AFP) production and invasive liver and lymph node metastases, typically associated with a poor prognosis. Although immuno-chemotherapy has made significant achievements in the conversion therapy of advanced GC in recent years, the management of HER2-negative, proficient mismatch repair (pMMR), and a programmed cell death ligand-1 (PD-L1) combined positive score (CPS)<5 cases, particularly in the context of synchronous multiple liver metastases and lymph node involvement, poses significant challenges. This is attributable not only to its rapid progression but also to its poor prognosis. We retrospectively report a case of HAS with concurrent multiple liver and lymph node metastases. Following six cycles of immuno-chemotherapy, R0 resection was achieved, and postoperative pathological examination confirmed a pathological complete response (pCR). No recurrence or metastasis was observed at the 32-month postoperative follow-up (last follow-up: April 26, 2025). To our knowledge, no previous reports have documented pCR in HER2-negative, pMMR, and PD-L1 CPS<5 patients with advanced HAS following conversion therapy with combined immuno-chemotherapy. This report aims to provide further clinical reference for the treatment of advanced HAS.Case summaryA 51-year-old male patient was diagnosed with HAS accompanied by multiple liver and lymph node metastases. Following six cycles of immunotherapy (sintilimab) combined with chemotherapy (Nab-paclitaxel, oxaliplatin, and S-1), the primary tumor exhibited significant reduction. Multiple liver metastases showed partial shrinkage or disappearance (the target lesion diameter must be less than 10 mm), and retroperitoneal lymph nodes were no longer detectable. After thorough evaluation, R0 resection was deemed achievable. Therefore, radical distal gastrectomy with D2 lymphadenectomy and liver metastasectomy were performed. Postoperative pathology confirmed pCR. The patient has remained progression-free survival (PFS) for 32 months and overall survival (OS) for 38 months, with no evidence of recurrence or metastasis.ConclusionHAS is a highly invasive malignant tumor of the stomach. The dynamic changes in AFP serve as a reliable indicator for detecting HAS, evaluating treatment efficacy, and predicting recurrence. In advanced HER-2-negative, PD-L1 CPS<5, pMMR-type HAS, employing a conversion therapy regimen combining sintilimab with Nab-paclitaxel, oxaliplatin, and S-1 may reduce tumor staging, enhance conversion therapy success rates, and prolong survival.